Immunothrombosis in Acute Respiratory Dysfunction of COVID-19 - Fang, Xiang-Zhi; Wang, Ya-Xin; Xu, Ji-Qain; He, Ya-Jun; Peng, Zhe-Kang; Shang, You (Frontiers in Immunology, 2021)
COVID-19 is an acute, complex disorder that was caused by a new β-coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Based on current reports, it was surprising that the characteristics of many patients with COVID-19, who fulfil the Berlin criteria for acute respiratory distress syndrome (ARDS), are not always like those of patients with typical ARDS and can change over time. While the mechanisms of COVID-19–related respiratory dysfunction in COVID-19 have not yet been fully elucidated, pulmonary microvascular thrombosis is speculated to be involved. Considering that thrombosis is highly related to other inflammatory lung diseases, immunothrombosis, a two-way process that links coagulation and inflammation, seems to be involved in the pathophysiology of COVID-19, including respiratory dysfunction. Thus, the current manuscript will describe the proinflammatory milieu in COVID-19, summarize current evidence of thrombosis in COVID-19, and discuss possible interactions between these two.